Text Hiding in Color Images Using the Secret Key Transformation Function in GF (2n) - Hussein M. Ali, Nada; Monem S. Rahma, Abdul; Salim Jamil, Abeer (Iraqi Journal of Science, 2023)
Steganography is one of the most popular techniques for data hiding in the different media such as images, audio or video files. This paper introduced the improved technique to hide the secret message using the LSB algorithm inside the RGB true color image by encrypting it using the secret key transformation function. The key is selecting randomly in the GF (2n) with condition it has an inverse value to retrieve the encrypted message. Only two bits are used for the low byte in each pixel (the blue byte) to hide the secret message, since the blue color has a weak effect on human eyes. The message hidden by the suggested algorithm is less vulnerable to be stolen than other similar applications.